Exploring the risk matrix of drug overdose deaths of young people: Drug use patterns, individual characteristics, circumstances, and environment - Rönkä, Sanna; Konttinen, Heta; Kriikku, Pirkko; Hakkarainen, Pekka; Häkkinen, Margareeta; Karjalainen, Karoliina (Elsevier BV, 2026)
Background: The number of drug-induced deaths among young people has increased in Finland in recent years, and their proportion of all drug-induced deaths is among the highest in Europe. The aim of the multidisciplinary study was to explore individual, situational and environmental factors contributing to drug overdoses of young people in a non-heroin use setting.
Methods: All drug overdose deaths (N = 300) of under 30-year-olds in Finland between 2019 and 2021 were investigated. The research material included police investigation reports, forensic autopsy reports, post-mortem toxicological reports, and death certificates. Public statistical indicators were used as secondary data.
Results: Of the deaths, 86.7 % were unintentional and 88.0 % were caused by poly-drug toxicity. In 53.7 %, substance use was recorded in the background documents, and 4.0 % had been in opioid agonist treatment at the time of death. The deceased had mental disorders in 51.6 % of the cases. Only 13.7 % were resuscitated by emergency care, as in most cases the person was either unresponsive or was found dead. The deceased lived in areas that are socially and economically disadvantaged compared to the average.
Conclusion: Overdose deaths of young people result from a complex matrix of risk factors. It appears that, the treatment system has not effectively addressed the needs of the deceased, and the retention of health and social care has been inadequate. Additionally, help seems to have been called too late. Tailored interventions that acknowledge the known risks of drug overdoses are needed as well as political decisions that enable harmreduction measures.